2007
DOI: 10.1007/s12011-007-8014-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Element Contents Between Gunshot Entry Wounds with Full-jacketed Bullet and Lead Bullet

Abstract: To elucidate characteristics of gunshot residues in gunshot entry wounds with full-jacketed and lead bullets, element contents in entry gunshot wounds and control skins were analyzed by inductively coupled plasma-atomic emission spectrometry (ICP-AES). It was found that a high content of Fe and Zn was deposited in the gunshot entry wounds with full-jacketed bullet, whereas a high content of Pb was deposited in the gunshot entry wounds with lead (unjacked) bullet. It should be noted that the content of Pb was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…In fact, these three elements, in the form of lead styphnate, barium nitrate, and antimony sulfide, are combined in a single application for one product: the mix in the primer cap of a cartridge casing. Moreover, GSR primer particles typically show a characteristic spherical shape: this particle morphology, when combined with the elemental composition, makes GSR quite distinct from many environmental particulates [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these three elements, in the form of lead styphnate, barium nitrate, and antimony sulfide, are combined in a single application for one product: the mix in the primer cap of a cartridge casing. Moreover, GSR primer particles typically show a characteristic spherical shape: this particle morphology, when combined with the elemental composition, makes GSR quite distinct from many environmental particulates [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the fatal bullet was not found or it was badly damaged, identification of the responsible firearm was enabled. A combination of element and lead isotope ratio analyses in gunshot entry wounds enabled to identify the used ammunition [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…The authors [3] previously investigated the concentrations of lead, zinc, copper, iron, antimony, barium, and nickel in gunshot entry wounds inflicted by both lead and fulljacketed bullets and found that the lead concentrations were significantly higher in gunshot entry wounds inflicted by lead bullets in comparison with those inflicted by full-jacketed ones. Moreover, the proportion of lead and copper, measured from retained bullets, were significantly different among the three types of bullet [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unjacketed bullets seem to leave much more radiopaque material when traveling through tissues [24], and radiography allows an accurate assessment of bone tissues, especially when images are observed at high magnification. In charred material it is at times common to find lesions which may look like a gunshot wound but may not be.…”
Section: Introductionmentioning
confidence: 99%